2021
DOI: 10.1093/jimb/kuab075
|View full text |Cite
|
Sign up to set email alerts
|

Insights into cyanobacterial alkane biosynthesis

Abstract: Alkanes are high-energy molecules that are compatible with enduring liquid fuel infrastructures, which make them highly suitable for being next-generation biofuels. Though biological production of alkanes has been reported in various microorganisms, the reports citing photosynthetic cyanobacteria as natural producers have been the most consistent for the long-chain alkanes and alkenes (C15–C19). However, the production of alkane in cyanobacteria is low, leading to its extraction being uneconomical for commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…Coates and collaborators (Coates et al 2014 ) characterized the distribution of hydrocarbon biosynthetic pathways across cyanobacteria. They concluded that most cyanobacteria, including Synechocystis 6803, harbor the two-step acyl-ACP reductase/aldehyde-deformylating oxygenase (Aar/Ado) pathway, producing C15 or C17 alkanes (Schirmer et al 2010 , Parveen and Yazdani 2022 ). Still, Aar enzymes were found to vary in activity, substrate specificity, and solubility with host habitat.…”
Section: Lipid Biosynthesismentioning
confidence: 99%
“…Coates and collaborators (Coates et al 2014 ) characterized the distribution of hydrocarbon biosynthetic pathways across cyanobacteria. They concluded that most cyanobacteria, including Synechocystis 6803, harbor the two-step acyl-ACP reductase/aldehyde-deformylating oxygenase (Aar/Ado) pathway, producing C15 or C17 alkanes (Schirmer et al 2010 , Parveen and Yazdani 2022 ). Still, Aar enzymes were found to vary in activity, substrate specificity, and solubility with host habitat.…”
Section: Lipid Biosynthesismentioning
confidence: 99%
“…The associations between SFAs and microcystin concentration in our elastic net models indicate that the relative abundances of SFAs shift during oxidative stress. SFAs accumulate between the lipid bilayers of cyanobacterial thylakoid and cytoplasmic membranes 50,88 where they contribute to membrane structure and help ne-tune localization of photosynthetic machinery 50 during temperature and light stress 49,50,89 . Cyanobacteria use an acyl-ACP reductase/aldehyde-deformylating oxygenase (ADO) pathway to produce fatty aldehydes of decreasing chain length (C n , C n-1 , C n-2 …; Fig 7).…”
Section: Microcystin Toxin Prediction Using the Volatilomementioning
confidence: 99%
“…Subsequently, ADO converts the aldehydes into 15- or 17-carbon alkanes (pentadecane or heptadecane, respectively) and formate (Fig. 1 ) [ 13 , 22 , 24 26 ]; ADO produces alkenes if the aldehyde substrates are monounsaturated. Notably, alkanes have been produced via heterologous expression of AAR and ADO in Escherichia coli , indicating that these enzymes are essential for alkane biosynthesis [ 13 , 22 ].…”
Section: Introductionmentioning
confidence: 99%